Social capital accumulation in Malaysia - Doris Padmini Selvaratnam,; Poo, Bee Tin; Norlaila Abu Bakar,; Nor Aini Hj. Idris,; Madeline Berma, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
The World Bank has identified social capital as the fourth factor to fuel economic growth after physical capital, financial capital and human capital. There are various social ills (for example, juvenile delinquency, crimes, murder, gangsterism, abandonment of the elderly, and domestic violence) plaguing the society today. This can be attributed to various factors ranging from peer pressure, mental problems, poverty, marginalisation and erosion of moral values. In a society that has experienced a rapid economic growth and a steady increase in the income per capita, it is thus an alarming factor if there is an increase in social problems and an increase in government expenditure to curb this problem. Social capital through effective networking is seen as an avenue to enhance positive social values and contribute towards a harmonious society